Insight into the nature and the transformation of the hydroxyl species in the CeY zeolite. Issue 7 (18th February 2022) - Hui, Yu; Zheng, Jian; Qin, Yucai; Du, Xiaohui; Zu, Yun; Yang, Jiabao; Sun, Shuhong; Gao, Xionghou; Sun, Zhaolin; Song, Lijuan
Abstract : The nature and transformation of hydroxyl species in a CeY zeolite during the calcination process have been investigated via the information of the hydroxyl spectra of the samples monitored in real-time via in situ FTIR spectroscopy technology. Abstract : The nature and transformation of each potential hydroxyl species in a Ce-modified Y zeolite during the calcination process have been investigated via the information of the hydroxyl spectra of the samples monitored in real-time via in situ FTIR spectroscopy technology. A thermogravimetric method was also used to identify the elementary transformation processes of the hydroxyl species during the calcination of the zeolite samples. The features of the bridging hydroxyl groups O(1)H in the supercage and O(2)H in the sodalite cages of Y zeolites are remarkably affected by the Ce species, causing red-shift of the FTIR spectrum peaks from 3635 cm −1 to 3622 cm −1 for the O(1)H bridging hydroxyl groups and from 3556 cm −1 to 3523 cm −1 for the O(2)H bridging hydroxyl groups. It is noteworthy to mention that the acidity of the bridging hydroxyl groups O(2)H in the six-membered rings shared by sodalite cages and supercages of CeY zeolites are remarkably affected by the Ce species located in sodalite cages. The introduction of Ce species into sodalite cages significantly inhibited the H/D exchange reactions of O(2)H with D2 O and C6 D6 probing molecules. These findings are crucial to get a better understanding of the roles of the rare earth (RE) species in influencing the hydrothermal stability and acidity of REY zeolites.